Colombia : Financial Sector Assessment Program-Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
There have been significant improvements to the legal framework and the supervisory process since the last Basel Core Principles (BCP) review; some additional recommended enhancements are highlighted in this assessment. The Superintendency of Financial Institutions (SFC) is an integrated supervisor with a purview that includes banks, finance companies, insurance, securities, and other financial intermediaries. Additionally, the SFC is also the bank resolution authority. To strengthen consolidated supervision, Congress passed Financial Conglomerates Law (FCL) 1870 addressing the supervision of financial conglomerates and granting the SFC supervisory authority over financial conglomerates (CF).2 The FCL strengthened the framework for consolidated supervision, which already included banks and their subsidiaries, by adding holding companies as supervised entities. Moreover, it defined the scope of supervision of financial conglomerates, setting standards with regards to risk management, adequate capital, and corporate governance, as well as minimum requirements for managing concentration risks and conflicts of interest in intragroup and related party exposures. The SFC has strong coordination and cooperation arrangements with foreign supervisors (through signed Memoranda of Understanding (MOUs) and the coordination mechanisms derived from the CCSBSO, among others) as well as the authority to request information from parent companies, all of which were further enhanced with the issuance of the FCL. Additionally, the SFC has access and authority to require information from ultimate beneficial owners.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Colombia